Years of potential life lost (YPLL) by Aids: Pernambuco, 1996 and 2005 - Lucena, Romualdo Mendonça de; Sousa, Jailson Lopes de (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: the Years of Potential Life Lost (YPLL) indicator offers a vision of not only the death cause, but also the age in which the cause produced the death, which makes possible the knowledge of, besides the quantity of deaths, their precocity. Objective: describe the behavior of aids mortality using the YPLL indicator in Pernambuco and its regions, in 1996 and 2005. Methods: a transversal-type descriptive study was done. To obtain the YPLL number a distribution of deaths was made in groups of age between 1 and less than 70 years old. Then, the number of deaths in each age group was multiplied by the number of remaining years to complete the limit age. The YPLL average per death was calculated as a division of the YPLL total by the number of deaths considered. Results: in Pernambuco, during the years of 1996 and 2005, there was a reduction (-0.75%) in the number of deaths caused by aids, in the number of YPLL (-6.20%), in the YPLL tax (-17.86%) and in the average of years lost for each death caused by aids (-5.52%). On the other hand, there was an increase of 5.21% on the average age of deaths from aids. Conclusion: Pernambuco is facing changes in the path of aids epidemic, being observed, in this study, two national trends of the epidemic: interiorizing and higher life expectancy of those affected by aids/HIV. From this analysis, it was also possible to perceive the importance of the YPLL indicator in the study of aids mortality, since that, although it has been observed an increase in the life expectancy, aids, as a specific cause of death, is still responsible for thousands of YPLL in Pernambuco.